Pengaruh Pengetahuan Perpajakan, Progra Pemutihan, dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Kendaraan Bermotor Kota Surakarta - Bening Karismawati; Rispantyo Rispantyo (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this study was to examine the effect of Tax Knowledge, Tax Amnesty Program, and Tax Sanctions on Motor Vehicle Taxpayer Compliance in Surakarta City. This study used motor vehicle taxpayers in Surakarta City. The method in this study uses a quantitative method. In this study, SPSS version 27.0 was used to analyze the data. The data sources used were primary data and secondary data. The population in this study were motor vehicle taxpayers in Surakarta City, totaling 517,790 vehicles registered according to the Surakarta City Central Statistics Agency. The sample in this study was 100 taxpayers, calculated using the Slovin formula. The sampling technique in this study used Accidential Sampling. The data collection technique used a questionnaire. In this study, descriptive analysis, multiple linear tests, t-tests, f-tests, and coefficient of determination tests were used. The results of this study stated that Tax Knowledge had no significant effect, meaning that tax knowledge had not been able to increase taxpayer compliance in paying motor vehicle taxes. Meanwhile, tax amnesty and tax sanctions have a significant positive effect, meaning that with the implementation of the amnesty program and the increasingly strict sanctions given, it will increase taxpayer compliance in paying motor vehicle taxes.